2007
DOI: 10.1242/jeb.006577
|View full text |Cite
|
Sign up to set email alerts
|

Histamine operates Cl–-gated channels in crayfish neurosecretory cells

Abstract: SUMMARY We describe a histamine-activated Cl– conductance in the X-organ neurons from crayfish Cherax quadricarinatus, which has comparable properties to the homomultimeric histamine-gated ion channels described in Drosophila. Topical application of histamine inhibited spontaneous neuronal firing in the X-organ sinus gland tract, concomitant with an increase in the membrane conductance. In X-organ neurons in culture and under voltage-clamp conditions, histamine evoked outward currents at –40 mV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…The recorded response to histamine's effect also served as the indicator for when the histamine receptor antagonists had fully blocked histamine responses. Although most histamine responses that have been examined in crustaceans are blocked by the H 2 receptor antagonist cimetidine (Bayer et al, 1989;Callaway and Stuart, 1989;El Manira and Clarac, 1994;Christie et al, 2004;Cebada and García, 2007;McCoole et al, 2011), it failed to block the responses to puffed histamine in either the CoG or the STG of H. americanus. We therefore tested a series of other histamine receptor antagonists, and found that the responses to puffs of histamine were blocked most effectively by a cocktail of two antagonists, the H 1 receptor antagonist transtriprolidine hydrochloride (Tocris Bioscience, Ellisville, MO, USA; catalog no.…”
Section: Electrophysiological Recordingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recorded response to histamine's effect also served as the indicator for when the histamine receptor antagonists had fully blocked histamine responses. Although most histamine responses that have been examined in crustaceans are blocked by the H 2 receptor antagonist cimetidine (Bayer et al, 1989;Callaway and Stuart, 1989;El Manira and Clarac, 1994;Christie et al, 2004;Cebada and García, 2007;McCoole et al, 2011), it failed to block the responses to puffed histamine in either the CoG or the STG of H. americanus. We therefore tested a series of other histamine receptor antagonists, and found that the responses to puffs of histamine were blocked most effectively by a cocktail of two antagonists, the H 1 receptor antagonist transtriprolidine hydrochloride (Tocris Bioscience, Ellisville, MO, USA; catalog no.…”
Section: Electrophysiological Recordingsmentioning
confidence: 99%
“…0662) and the H 2 receptor antagonist ranitidine hydrochloride (Tocris Bioscience; catalog no. 1967), both of which have been shown to block some crustacean histamine receptors (Callaway and Stuart, 1989;Cebada and García, 2007); the cocktail consisted of 10 −6 to 5×10…”
Section: Electrophysiological Recordingsmentioning
confidence: 99%
“…FMRFamide-IR in P. japonica (Ohsuga et al, 2000) and now H. crassicornis. Finally, based on evidence from arthropods, it is possible that some of the physiological experiments implicating GABA as the neurotransmitter in the hair cells could have been a consequence of GABA activating HA-gated chloride channels (McClintock & Ache, 1989;Cebada & García, 2007). This cross-activation has been described twice, although in both cases it was not susceptible to bicuculline (Kita, Irie, Nomura, Ozoe, & Ozoe, 2017;Gisselmann, Plonka, Pusch, & Hatt, 2004…”
Section: Vestibular Systemmentioning
confidence: 99%
“…Ingestion of food containing histamine can cause histamine poisoning with allergic‐like symptoms such as nausea, vomiting, diarrhea, hives, itching, red rash and hypotension . In crustaceans, histamine may not only be produced by bacteria, but is also naturally present and acts as a neurotransmitter . The United States Food and Drug Administration (US FDA) has set the maximum level of histamine in seafood as 50 µg g −1 (wet weight)…”
Section: Introductionmentioning
confidence: 99%